Antifungal activity of the volatile organic compounds produced by Ceratocystis fimbriata strains WSJK-1 and Mby - Gao, Yang; Ren, Huan; He, Shuqi; Duan, Shanquan; Xing, Shijun; Li, Xue; Huang, Qiong (Frontiers in Microbiology, 2022)
Microorganism-produced volatile organic compounds (VOCs) are considered promising environmental-safety fumigants in food preservation. In this study, the VOCs from fungal Ceratocystis fimbriata strains (WSJK-1, Mby) were tested against postharvest fungi M. laxa, F. oxysporum, M. fructicola, B. cinerea, A. solani and A. flavus in vitro. the mycelial growth was significantly inhibited, in particular M. fructicola and B. cinerea (76.95 %, 76.00 %), respectively. VOCs were identified by headspace solid-phase microextraction coupled with Gas Chromatography-Mass Spectrometry (HS-SPME-GC–MS), 41 compounds were identified. The antifungal activity of 21 compounds were tested by the minimum inhibitory concentrations (MIC) value. Among them Benzaldehyde, 2-Phenylethanol and 1-Octen-3-ol showed strong antifungal activity with the MIC in vitro ranging from 0.094 to 0.284 mL L−1 depending on the pathogen tested. The optical microscope showed serious morphological damage, including cell deformation, curling, collapse and deficiency in cell structures of mycelial or conidia treated with C. fimbriata VOCs and pure compounds. In vivo tests, C. fimbriata VOCs decreased brown rot severity in peaches, and compounds Benzaldehyde and 2-Phenylethanol could reduce peach brown rot in peaches at the concentration of 60 μL L-1. The VOCs produced by C. fimbriata strain have good antifungal effects, low concentration fumigation could control peach brown rot. Its fragrance is fresh, safe and harmless, and it is possible to replace the chemical fumigants and could be used as a potential biofumigant to control fruit postharvest transportation, storage and food preservation. To the best of our knowledge, this is the first report on the antifungal activity of VOCs produced by C. fimbriata.